Dental Care in Risk Groups of Patients with Mental Disorders and Epilepsy - Z. Halačková; L. Izakovičová Hollá; M. Kukletová (Czech Dental Chamber, 2009)
The aim of our study was to determine quality of dental care in handicapped persons, first of all in patients with the diagnosis of mental retardation and epilepsy. Over the period of 2002-2004, 225 risk patients, who were sent to the Clinics of Stomatology, St. Anne's University Hospital in Brno for treatment, were examined. Of this number, 104 persons were the patients with the diagnosis of mental retardation and epilepsy and these were split into four subgroups. The first two groups included patients only with the diagnosis of mental retardation or epilepsy, the other two groups contained persons in whom these diseases were combined with another disease. The incidence of dental caries and their treatment was recorded by KPE and RI in both the groups. Compared to the nationwide survey where the average values of 1.79 caries per patient were determined, the average values in the studied set were fourfold higher. There was not any difference in the incidence of caries between the mentally retarded persons, epileptics and the patients in whom epilepsy was combined with another disease. The groups of patients with mental retardation or with this diagnosis in combination with another disease had lower average values of number of fillings (3.43 and 3.64, respectively) than the patients with the diagnosis of epilepsy and epilepsy combined with another general disease (4.47 and 5.50, respectively). KPE values in all the studied groups were high; the group with the diagnosis of mental retardation and mental retardation combined with another disease had lower values (16.66 and 17.48, respectively) than the group of patients with the diagnosis of epilepsy and epilepsy combined with another disease (21.33 and 19.03, respectively). Percentage values of level of treatment in patients with different diagnoses showed low level of treatment in all the studied groups; percentage values of RI were the lowest in the group of patients with mental retardation in combination with another disease or mental retardation alone (32.36 and 34.37, respectively). Our study points to insufficient treatment of the handicapped patients and necessity to improve dental care in these patients.